Hubungan Asupan Makanan Dengan Kenaikan Berat Badan Ibu Hamil Di Wilayah Kerja Puskesmas Lingkar Timur Kota Bengkulu - Asmawati Asmawati; Wenny Irma; Dahrizal Dahrizal (JURNAL KEPERAWATAN RAFLESIA, 2021)
Pregnant’s nutritional intake is one of the most factors that affects the health of pregnant and the newborns. This study aims to identificate the correlation food intake and weight gain during one month of pregnancy in the community health center of ​​Lingkar Timur Bengkulu. The research design was a cross-sectional. Sampling technique were consequtive sampling with a total of 79 pregnant woman. The weight gain observed during one month. Data of intake nutrition taken by quissionaire from self management nutrition (SMN) instrument that consist 25 item of questions. The result showed 63 (79,75%) pregnant women have suitable weight gain of Institute of Medicine (IOM) recommendation and 47 (59,49 %) had good food intake. Of 47 or 84.0% pregnant women who had good food intake, she had a suitable weight gain with IOM recommendation. The analysis chi-square showed there is a correlation between food intake and weight gain in one month of pregnancy (p-value 0.039 < α ≤0.05). The nutrition intake is important for increase a suitable of weight gain during pregnant periode.